2022
DOI: 10.22541/au.164268225.58156045/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring zero water level in stream reaches: A comparison of an image-based versus a conventional method

Abstract: Process understanding of the interaction between streamflow, groundwater and water usages under drought are hampered by a limited number of gauging stations, especially in tributaries. Recent technological advances facilitate the application of non-commercial measurement devices for monitoring environmental systems. The Dreisam River in the South-West of Germany was affected by several hydrological drought events from 2015 to 2020, when parts of the main stream and tributaries fell dry. A flexible longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study suggested that temperature sensors always determined the dry and not-dry flow state correctly (based on visual flow state observations) (Constantz et al, 2001). Comparisons of dry and not-dry flow states between water level logger data and pre-processed time-lapse camera images led to concordant observations if the water level logger indicated a dry stream (true positive rate: 100%), but if the water level logger measurements indicated a not-dry condition, observations diverged by 48%-85% (Herzog et al, 2022). A national hydrography dataset of stream permanence classifications disagreed one-quarter of the time with flow state assessments from topographic maps or aerial imagery and interviews with residents, with the disagreement being higher for smaller streams (Hafen et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Another study suggested that temperature sensors always determined the dry and not-dry flow state correctly (based on visual flow state observations) (Constantz et al, 2001). Comparisons of dry and not-dry flow states between water level logger data and pre-processed time-lapse camera images led to concordant observations if the water level logger indicated a dry stream (true positive rate: 100%), but if the water level logger measurements indicated a not-dry condition, observations diverged by 48%-85% (Herzog et al, 2022). A national hydrography dataset of stream permanence classifications disagreed one-quarter of the time with flow state assessments from topographic maps or aerial imagery and interviews with residents, with the disagreement being higher for smaller streams (Hafen et al, 2020).…”
Section: Discussionmentioning
confidence: 98%